E PluriBus Unum: High Performance Connectivity on Buses — Extended version - Mahajan, Ratul; Padhye, Jitu; Agarwal, Sharad; Zill, Brian (2009)
We present PluriBus, a system to provide high performance Internet access on-board moving vehicles. It seamlessly combines multiple wide-area wireless paths with disparate loss and delay characteristics. PluriBus employs opportunistic erasure coding, a novel technique to use spare capacity along any path to mask losses from end hosts. It sends erasure coded packets only when there is an instantaneous opening in a path's spare capacity, so that coded packets do not steal capacity from data packets. Packets are coded using a new erasure code that we have developed to greedily maximize the amount of data recovered with each opportunity to send a coded packet. We have deployed PluriBus on two buses. Our experiments show that it reduces the median flow completion time by a factor of 2.5, compared to an existing method for spreading traffic across multiple paths.